Studi Eksperimental Pemanfaatan Limbah Partikel EPS dan Serbuk Cangkang Telur Untuk Komposit Tanah yang Berkelanjutan - Maulida, Syifa Laila; Setya, Tiane; Syahril, Syahril (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Soft clay soil has low bearing capacity and high compressibility, which can cause structural damage. On the other hand, Expanded Polystyrene (EPS) waste and eggshell waste are abundant and difficult to decompose, making them potential materials for sustainable soil stabilization. This study aims to improve the physical and mechanical properties of soft clay by adding EPS particles at 0.45% of the dry soil weight and eggshell powder at 4%, 8%, and 12%. Soil samples were obtained from Mekarmukti Village, West Bandung Regency, then cured for 0–28 days and tested through water content, specific gravity, standard compaction, unconfined compressive strength (UCS), and California Bearing Ratio (CBR) tests. The results showed that the mixture reduced water content, increased density, and improved soil strength. The optimum composition was achieved with soil + 0.45% EPS + 8% eggshell powder, where the unconfined compressive strength increased from 1.631 kg/cm² to 2.662 kg/cm², the unsoaked CBR increased from 2.201% to 4.659%, and the soaked CBR reached 1.458%. The mixture produced lighter, more stable, and easily compacted soil, and is recommended as an environmentally friendly stabilization material for lightweight embankments, bridge approaches, and construction on soft ground.